Diseases of ginger (Zingiber officinale Rosc.) and their management - DAKE, G N (Journal of Spices and Aromatic Crops, 1995)
Ginger (Zingiber officinale Rose.) suffers from 24 diseases of fungal, bacterial, viral and mycoplasmal origin. Of them, soft rot (Pythium aphanidermatum), yellows (Fusarium oxysporum f. sp. zingiberi), bacterial wilt (Pseudomonas solanacearum), Phyllosticta leaf spot (Phyllosticta zingiberi) and storage rot by many pathogenic, saprophytic fungi and bacteria are of economic importance because of their potential to cause great losses to ginger production. The constraints in disease management and the strategies that have been developed to manage the diseases involving’ cultural, chemical and biological methods combined with soil solarization are discussed. Future options for the management of ginger diseases by integration of conventional strategies with modern biotechnological means for effective control measures are also discussed.